"Reversible cytotoxic lesion of the corpus callosum following SARS-CoV-2 mRNA vaccine administration: a finding to be aware of". Issue 6 (December 2022) - Procaccini, Luca; Mincuzzi, Erica; Bernardini, Antonio; Franchi, Paola; Voicu, Ioan P; Caulo, Massimo
Cytotoxic lesions of the corpus callosum (CLOCCs) are a clinical-radiological spectrum of disorders secondary to several etiopathogeneses. Cytotoxic lesions of the corpus callosum are typically associated with mild clinical symptoms including fever, headache, confusion, and altered mental status. We present a case of a 51-year-old Caucasian woman who developed a reversible lesion of the splenium of the corpus callosum associated with small round-shaped white matter hyperintensities after the first dose of SARS-CoV-2 mRNA vaccine. Magnetic resonance imaging is fundamental for diagnosis and no treatment is generally required.